Uveitis in spondyloarthritis: current possibilities of anti-inflammatory therapy - A. A. Godzenko; N. L. Sheremet; E. L. Nasonov (Научно-практическая ревматология)
Uveitis is a common extra-skeletal manifestation of ankylosing spondylitis (AS) and other spondyloarthritis (SpA). The recurrent course of uveitis in SpA contributes to the development of complications affecting vision. Timely treatment of uveitis exacerbation and prevention of relapses is an important component of SpA management. The article discusses approaches to modern anti-inflammatory therapy of uveitis in SрA, including traditional and targeted drugs. The data from clinical studies on the effect of various treatment regimens on the course of uveitis in SpA are presented, as well as a comparative assessment of the effectiveness of biologic and targeted synthetic drugs.